التحديات التي تواجه رأس المال الاجتماعي للأسرة الفلسطينية "دراسة سيكولوجية للأسرة الفلسطينية في زمن ما بعد الحداثة - 'Ahmed Khalid Al-Zatari; Sana' Zahir Abdul Al-wali Al-Rafu' (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceedings Of The International Conference On Da’wah And Islamic Management (IC-DAIM 2021) “Humane Leadership and Da’wah For Sustainable Future of Ummah” 26-27 October 2021 Organized by: Da’wah and Islamic Management Program, Faculty of Leadership and Management, USIM